Serum Heparanase: A New Clinical Biomarker Involved in Senile Metabolic Inflammatory Syndrome - Zhou X (Dove Medical Press, 2021)
Qingsong Wang,1 Xiu-ling Zhou,2 Guang-hai Mei,3 Jiantao Wang,1 Zhongyu Yu,1 Yue Hu,1 Xinyu Guo,1 Hanyu Zhang,1 Xiaodie Xu,4 Chengfeng He,4 Jingchun Guo,4 Yinghong Tao,5 Houguang Zhou1 1Department of Geriatrics, Huashan Hospital, National Clinical Research Center for Aging and Medicine, Fudan University, Shanghai, 200040, People’s Republic of China; 2Department of Ultrasonics, Huashan Hospital, Fudan University, Shanghai, 200040, People’s Republic of China; 3Department of Neurosurgery, Huashan Hospital, Fudan University, Shanghai, 200040, People’s Republic of China; 4National Key Laboratory of Medical Neurobiology, Institute of Brain Science, Fudan University, Shanghai, 200030, People’s Republic of China; 5Department of Medical Examination Center, Huashan Hospital, Fudan University, Shanghai, 200040, People’s Republic of ChinaCorrespondence: Houguang ZhouDepartment of Geriatrics of Huashan Hospital, National Clinical Research Center for Aging and Medicine, Fudan University, No. 24 Ward, Building 6, No.12 Middle WuLuMuQi Road, JingAn District, Shanghai, 200040, People’s Republic of ChinaTel +86-21-52887246Email zhouhouguang@huashan.org.cnYinghong TaoDepartment of Medical Examination Center of Huashan Hospital, Fudan University, Building 4, No. 12 Middle WuLuMuQi Road, JingAn District, Shanghai, 200040, People’s Republic of ChinaTel +86-21-52889087Email taoyinghong@huashan.org.cnAim: Metabolic inflammation syndrome (MIS) can lead to a series of complications, but its exact inflammatory mechanism is still unclear. The aim of this study was to explore the correlation between heparanase (HPA) and MIS, and the close relationship between HPA and other chronic low-grade inflammation index, such as C-reactive protein (CRP) and interleukin-6 (IL-6).Methods: A total of 105 patients with MIS in the physical examination population of Huashan Hospital affiliated to Fudan University from May to June 2018 were selected as the MIS group, and 52 patients who were relatively healthy during the same period were used as the control group. The basic clinical data of the selected candidates were collected, the levels of serum HPA, CRP and IL-6 were measured by ELISA, and the levels of blood glucose and blood lipids were also detected.Results: Compared with the control group, the levels of HPA, CRP, IL-6, FBG, HbA1C, and TG of MIS group were all significantly elevated (all P< 0.05), and HDL-C levels were considerably reduced (P< 0.05). Correlation analysis showed that there was a noticeably positive correlation between serum HPA level and CRP, IL-6 levels (P< 0.05).Conclusion: Higher HPA levels might play a certain role in the occurrence and development of MIS. There was a certain close correlation between serum HPA level and CRP and IL-6 levels, and which indicated that HPA was involved in the chronic low-grade inflammatory reaction process of MIS.Keywords: metabolic inflammatory syndrome, MIS, heparanase, HPA, C-reactive protein, CRP, interleukin-6, IL-6, chronic low-grade inflammation, CLGI